1999
DOI: 10.1162/089892999563319
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Induced Changes in Associative Memory

Abstract: The notion that dreaming might alter the strength of associative links in memory was first proposed almost 200 years ago. But no strong evidence of such altered associative links has been obtained. Semantic priming can be used to quantify the strength of associative links between pairs of words; it is thought to measure the automatic spread of activation from a "node" representing one word to nodes representing semantically related words. Semantic priming could thus be used to test for global alterations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
137
6
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 242 publications
(160 citation statements)
references
References 49 publications
11
137
6
6
Order By: Relevance
“…There is also a growing literature on the association between REM and declarative memory processes that go beyond strengthening new episodic memories. For instance, REM has been associated with increased semantic priming of distantly related pairs of words (Stickgold, Scott, Rittenhouse & Hobson, 1999;Carr & Nielesen, 2015), problem solving through activation of broad associative semantic networks (Walker, Liston, Hobson & Stickgold, 2002;Cai et al, 2009), and extraction of statistical patterns in learning (Barsky et al, 2015). Our data are consistent with the view that REM activates broad semantic networks and allows the integration of new memories with remotely related existing knowledge.…”
Section: Discussionsupporting
confidence: 84%
“…There is also a growing literature on the association between REM and declarative memory processes that go beyond strengthening new episodic memories. For instance, REM has been associated with increased semantic priming of distantly related pairs of words (Stickgold, Scott, Rittenhouse & Hobson, 1999;Carr & Nielesen, 2015), problem solving through activation of broad associative semantic networks (Walker, Liston, Hobson & Stickgold, 2002;Cai et al, 2009), and extraction of statistical patterns in learning (Barsky et al, 2015). Our data are consistent with the view that REM activates broad semantic networks and allows the integration of new memories with remotely related existing knowledge.…”
Section: Discussionsupporting
confidence: 84%
“…Less apparent is why during PS the ERPs to pseudowords, but not incongruous words, resembled those to congruous words. The authors suggest that these results are consistent with the finding by Stickgold, Scott, rittenhouse, & Hobson (1999) that linguistic absurdity is accepted in a different manner in dream-sleep than during waking, as reflected by an abnormal pattern of semantic behavioral priming (upon being awoken from PS) where weak primes show greater effects than strong primes. However, it is unclear why this pattern, for which the equivalent in the Perrin study would be reduced N400s to more weakly associated words, would not also hold for the incongruous words as well as for the pseudowords.…”
Section: Erps During Sleepsupporting
confidence: 83%
“…4), sleep deprivation (SD) impairs affectively guided decision making (Pace-Schott et al 2012), moral reasoning ), insight (Wagner et al 2004), and creativity (Cai et al 2009;Home 1988). Based on the 'carry-over effect' after awakening (during which performance is altered as a result of the brain's slow transition to full wakefulness), elegant studies by Stickgold and colleagues showed that subjects awoken from REM sleep had a 32 % advantage in the number of anagrams solved (Walker et al 2002) and also showed greater priming by weak primes (e. g., thief-wrong) than by strong primes (e.g., hot-cold), contrary to the pattern of priming observed during wakefulness (Stickgold et al 1999). These data are consistent with a hyperassociative state of the mind during REM sleep.…”
Section: Insight and Creativitymentioning
confidence: 97%